Between Co-existence and Conflict: Understanding Antisemitism among Muslims in Norway (KULT_online, 2025)
Vibeke Moe Bjørnbekk’s Narratives about Jews among Muslims in Norway is a unique exploration of the narratives surrounding Jewish-Muslim relations in Norway. The book examines Muslim attitudes and perceptions of Jews in Norway, tracing these views from their earliest historical interactions to contemporary society through interviews. While the book successfully sheds light on important aspects of the topic, it falls short by remaining somewhat superficial in its analysis of the historical events discussed.